UTILIZATION OF EDUCATIONAL GAMES AS LEARNING MEDIA: RECOGNIZE THE CONCEPT OF NUMBERS - Afrianti, Rosa; Maryatun, Ika Budi (Universitas Labuhanbatu, 2025)
Purpose – This study explores the effectiveness of Android-based educational games in improving young children's number concept recognition. It examines key design elements contributing to successful early numeracy development and compares game-based learning with traditional teaching methods. The study also identifies challenges and opportunities in implementing digital games in early childhood mathematics education.Methodology – A Systematic Literature Review (SLR) was conducted following the PRISMA framework, including identification, screening, eligibility, and inclusion stages. Studies from 2019 to 2024 were selected using Scopus, Web of Science, and Google Scholar databases. A total of 30 high-quality, peer-reviewed journal articles met the inclusion criteria and underwent content analysis to extract key findings.Findings – The results indicate that Android-based educational games enhance number recognition through interactive, adaptive, and gamified learning experiences. Key design elements include multisensory engagement, immediate feedback, and adaptive difficulty levels. Comparisons with traditional teaching suggest that educational games offer greater motivation and individualized learning but require careful design for optimal impact.Contribution – This study provides insights into the pedagogical effectiveness of game-based learning in early childhood numeracy. It highlights best practices for designing educational games and recommends integrating digital tools into mathematics instruction.